Age- and gender-related incisor changes in different vertical craniofacial relationships - Amal I Linjawi (Wolters Kluwer Medknow Publications, 2016)
Objective: To investigate the age- and gender-related changes in upper and lower incisors' position and inclination in different vertical craniofacial relationships. Materials and Methods: A retrospective study on patients' records of age 8-48 years. The sample was divided based on Frankfort mandibular plane angle into three groups; normal, high, and low angle groups. It was then subdivided according to age. Upper and lower incisors' inclinations and positions were assessed from lateral cephalometric radiographs. Gender and age associations and effects size were calculated using two-way ANOVA tests. Significance level was set at P < 0.05. Results: Four hundred and twenty records (F = 272, M = 148) were included; 115 had normal, 81 low, and 250 had high vertical relationships with no significant age and gender distribution differences (P > 0.05). All significant associations and effects were found in the low angle group only. A significant association was found between gender and upper incisor inclination (P < 0.05) with medium effect size (0.13 ≤ ηp 2 < 0.26). An association is also found between age × gender interaction and upper incisor inclination and lower incisor position (P < 0.05) with large effect size (0.26 ≤ ηp 2 ). Conclusion: Age- and gender-related upper and lower incisor changes were found to be significant in subjects with decreased vertical skeletal pattern only. The upper incisor inclination and the lower incisor position were the most affected variables with age and gender.